FEMALE VULNERABILITY TO CLIMATE CHANGE DURING PANDEMIC IN INDIA (Prakriti - The International Multidisciplinary Research Journal, 2024)
Vulnerability, as stated in the IPCC report (2014), refers to the sensitivity of the system to the  adverse impacts of climate change and variability. It encompasses the sensitivity, resilience,  fidelity and general characteristics of the system (Alhassan et al., 2019). This paper explores how  gender and relationships affect vulnerability and change in the context of climate change (Olmos,  S., 2001). Marginalized communities face poverty and constraints, including climate impacts, and  are increasingly stressed in their daily lives. This study investigates India’s climate and its impact  on households, especially female-headed households, which often lack sufficient resources to  address population growth, land problems and environmental degradation. Women are more  vulnerable to climate-related events such as floods, floods and earthquakes because social,  economic and political constraints limit their ability to protect themselves. Studies show that  women and girls are less healthy than men when they are malnourished. There is an urgent need  to develop gender-sensitive strategies to address human security issues and the environmental and  human health problems resulting from climate change. Studies show differences in the roles,  access to resources, rights, knowledge and opportunities of men and women in combating climate  change. Despite the negative impact of global pandemics and social problems, women’s  participation in decision-making processes related to climate change is still limited. A study by the  World Health Organization has indicated that climate change is expected to lead to a decline in  agriculture in India by 2050, with wheat production expected to fall by 18.6% and rice yields by  10.8%. In India, women make up over 60% of the agricultural workforce and are responsible for  90% of post-harvest work. When it comes to water, a UNICEF report shows that women and girls  in India spend over 150 million hours a day collecting water, equivalent to the labor force of 1 million people.
Keywords: COVID-19 pandemic.; Maharashtra; Punjab